How Are Women Giving Birth in Healthcare Facilities Treated?. Issue 1 (January 2017) - Callister, Lynn Clark
Abstract : Implementation of the United Nations Sustainable Development Goals has increased emphasis in the global community on the social determinants of health. One growing concern worldwide is disrespectful and abusive care given to women while giving birth in healthcare facilities in some areas of the world.